Masculinidades : a emergência da estética militar como representação nas páginas do Jornal das Moças (1944-1945) - Trento, Patrick Aparecido (2017)
This research aims to analyze the representations of masculinity manifested by the magazine Jornal das Moças (1914 - 1965), between the years of 1944 and 1945, a period that includes Brazilian participation in World War II (1939-1945). Militarized aesthetics as a suitable masculine model. Among absences and presences in the periodical discourse, it drafts a prospect that the corporal forms pervaded by fashion and appearance are interwoven with the state and social gender policies, in the constitution of masculinity models adjusted and alternative to representations restrained in the Jornal das Moças?s pages